No Slam Dunk : Gender, Sport and the Unevenness of Social Change - Cooky, Cheryl; Messner, Michael A. (Book collections on Project MUSE., 2018)
Sport has undergone a radical gender transformation. However, the authors suggest, progress toward gender equity in sports is far from complete. The continuing barriers to full and equal participation for young people, the far lower pay for most elite-level women athletes, and the continuing dearth of fair and equal media coverage all underline how much still has yet to change before we see true gender equality in sports. The chapters in this text show that is this not simply a story of an "unfinished revolution." Rather, they contend, it is simplistic optimism to assume that we are currently nearing the conclusion of a story of linear progress that ends with a certain future of equality and justice. This book provides theoretical and empirical insights into the contemporary world of sports to help explain the unevenness of social change and how, despite significant progress, gender equality in sports has been no slam dunk.--description provided by publisher